Production of peptides with angiotensin-I converting enzyme (ACE) inhibitory properties from stichopus horrens - Saari, Nazamid; Ebrahimpour, Afshin; Forghani, Bita (2013)
The present invention pertains to a process for manufacturing a proteolysate with angiotensin converting enzyme (ACE)-inhibitory properties for sea cucumbers, and to the isolate produced according the method of the invention as well as peptides isolated therefrom which have ACE inhibitory properties. Therefore, furthermore is provided a method of identifying ACE inhibitory peptides from the proteolysate of the invention. The invention also relates to the peptides isolated using the screening method and the ACE inhibitory proteolysate of the invention. The products of the invention are particularly useful for the prevention of cardiovascular related diseases and thus can be used as food additives or supplements.